Tomato Wall-Associated Kinase SlWak1 Depends on Fls2/Fls3 to Promote Apoplastic Immune Responses to Pseudomonas syringae - Zhang, Ning (2020)
Wall-associated kinases (Waks) are important components of plant immunity against various pathogens, including the bacterium Pseudomonas syringae pv. tomato (Pst). However, the molecular mechanisms of their role(s) in plant immunity are largely unknown. In tomato (Solanum lycopersicum), wall-associated kinase 1 (SlWak1), has been implicated in pattern recognition receptor (PRR)-triggered immunity (PTI) because its transcript abundance increases significantly after treatment with the flagellin-derived, microbe-associated molecular patterns flg22 and flgII-28, which activate the PRRs Fls2 and Fls3, respectively. We generated two SlWak1 tomato mutants (Δwak1) using CRISPR/Cas9 gene editing technology and investigated the role of SlWak1 in tomato–Pst interactions. Late PTI responses activated in the apoplast by flg22 or flgII-28 were compromised in Δwak1 plants, but PTI at the leaf surface was unaffected. The Δwak1 plants developed fewer callose deposits than wild-type plants, but retained early PTI responses such as generation of reactive oxygen species and activation of mitogen-activated protein kinases upon exposure to flg22 and flgII-28. Induction of Wak1 gene expression by flg22 and flgII-28 was greatly reduced in a tomato mutant lacking Fls2 and Fls3, but induction of Fls3 gene expression by flgII-28 was unaffected in Δwak1 plants. After Pst inoculation, Δwak1 plants developed disease symptoms more slowly than Δfls2.1/2.2/3 mutant plants, although ultimately, both plants were similarly susceptible. SlWak1 coimmunoprecipitated with both Fls2 and Fls3, independently of flg22/flgII-28 or of BRASSINOSTEROID INSENSITIVE1-ASSOCIATED RECEPTOR KINASE1. These observations suggest that SlWak1 acts in a complex with Fls2/Fls3 and is important at later stages of PTI in the apoplast.